Alan P. Merriam versus Mantle Hood dalam Orientasi Studi Etnomusikologi - Slamet Riyadi (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2002)
The anthropological and musicological approaches of ethnomusicology have been extensively discussed by ethnomusicologists. In revealing musical facts, the anthropoÂlogical approach tends to discern music as a human behavior phenomenon. Meanwhile, the musicological approach considers music as exclusively musical matter.